Extension Contact and Extension Participation of Livestock Farmers in Jalandhar District of Punjab- A Benchmark Analysis - Gupta, Rohit; Singh, Kuldeep; Bhadauria, Pragya; Jadon, Y S (Indian Journal of Extension Education, 2020)
A study of the socioeconomic aspects of livestock farmers is a prerequisite for the appropriate design and successful execution of government’s developmental programmes. The present study was conducted to assess the socio-economic status and credibility of various extension activities among the livestock farmers. For this, primary data was collected through structured interview schedule using a sample size of 150 respondents from Jalandhar district of Punjab. Most of the respondentÂ (92.70%) have their strong linkage with Panchayat members and participation in various extension activities were found highest (19.10%) among young farmers. Majority of the farmers participated in Kisan melas (68.70%) albeit relative credibility index was found highest for demonstration activity. Hence efforts should be undertaken by the Government, Veterinary Universities and other extension agencies in providing information on improved livestock farming practices, result oriented extension activities and strong farmer-extension-research-linkages so that farmers could bring about change inÂ their living standard and can improve their socio-economic status.